2020
DOI: 10.1007/s10620-020-06508-8
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Closure Utilizing Endoloop and Endoclips After Gastric Endoscopic Submucosal Dissection for Patients on Antithrombotic Therapy

Abstract: Objectives Antithrombotic therapy is a well-known independent risk factor for bleeding after endoscopic submucosal dissection (ESD) of early gastric cancer (EGC). A novel method of ulcer base closure using an endoloop and endoclips has been reported. This study aimed to evaluate the effectiveness of endoscopic closure using an endoloop and endoclips in preventing post-ESD bleeding in patients undergoing gastric ESD on antithrombotic therapy. Methods This was a single center, retrospective study. Patients on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 26 publications
(33 reference statements)
0
53
0
Order By: Relevance
“…18 In addition, follow-up endoscopy has revealed that 52% (36/69) of defects closed with endoloops and hemoclips showed dehiscence. 21 On the other hand, the experiment in in vivo porcine models demonstrated that all of the post-ESD gastric mucosal defects were completely closed by EHS, remained closed without dehiscence, and healed histologically within 2 weeks. 24 In a multicenter prospective study of EHS for post-ESD gastric mucosal defects, mucosal closure by EHS was completed in 29 (97%) of 30 cases and was well maintained on POD 3 in 25 (84%) cases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…18 In addition, follow-up endoscopy has revealed that 52% (36/69) of defects closed with endoloops and hemoclips showed dehiscence. 21 On the other hand, the experiment in in vivo porcine models demonstrated that all of the post-ESD gastric mucosal defects were completely closed by EHS, remained closed without dehiscence, and healed histologically within 2 weeks. 24 In a multicenter prospective study of EHS for post-ESD gastric mucosal defects, mucosal closure by EHS was completed in 29 (97%) of 30 cases and was well maintained on POD 3 in 25 (84%) cases.…”
Section: Discussionmentioning
confidence: 97%
“…[17][18][19][20][21] In these techniques, hemoclips are typically used because of their availability; however, clip-mediated closure does not appear to be satisfactory as a complete countermeasure for postoperative bleeding, especially in gastric lesions, because it is often difficult to achieve complete closure and keep the defects closed without dehiscence. 17,18,21 We developed endoscopic hand suturing (EHS), which is a suturing technique using a needle holder and a curved needle attached to an absorbable barbed suture. 22,23 Previously, we have reported the feasibility and efficacy of EHS in porcine models and clinical studies in gastric ESD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, liver cirrhosis and ischemic heart disease were only significantly associated with late bleeding. On recognizing the risk factors for early/late bleeding, the closure of a mucosal defect would be a possible countermeasure especially for early bleeding, 26 although it has not proved enough without established technique, 27 and delaying discharge can be considered for patients at risk of late bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…First, the defect closure is technically difficult by using endoscopic clips, which is the most familiar device for tissue apposition [16]. For the closure of large defects, purse-string closure with a detachable snare and clips is feasible, although it will finish a tentative closure [17]. Second, even though the defect is closed, it is easily dehisced in a short period.…”
Section: What's Further Advancement Of Esd?mentioning
confidence: 99%